Differential regulation of NSC phenotype and genotype by chronically activated microglia within cocultures. Issue 11 (10th October 2016) - Farrell, Kurt; Borazjani, Ali; Damaser, Margot; Kothapalli, Chandrasekhar R.
Abstract : Under disease or injury conditions in the central nervous system (CNS), activated microglia release cytokines and chemokines to modulate the microenvironment and influence tissue remodeling. Abstract : Under disease or injury conditions in the central nervous system (CNS), activated microglia release cytokines and chemokines to modulate the microenvironment and influence tissue remodeling. To exploit the full potential of neural stem cell (NSC) transplantation approaches, a permissive microenvironment needs to be created for their survival, homing and differentiation. To investigate the role of chronically activated microglia in the fate of NSCs, spontaneously immortalized murine microglial cells (SIM-A9) were cocultured with embryonic murine cortical NSCs on 2D substrates or within 3D gels. Standalone NSC cultures served as controls. Cytokines and chemokines released by NSCs and SIM-A9 cells in standalone and cocultures were quantified. Coculturing with SIM-A9 cells suppressed NSC viability, neurite outgrowth, neural differentiation and TUJ1 gene expression, and promoted glia formation in both 2D and 3D cultures, over a 10-day period. The seven most-abundantly released analytes by microglia (MCP-1, MIP2, G-CSF, MIP-1α, MIP-1β, TNF-α, IL-6) were tested for their individual effects on NSCs, to investigate if the outcomes in cocultures were due to the synergistic effects of analytes or the influence of any individual analyte. All the seven analytes significantly suppressed cell survival compared to controls, but exposure to MIP-1β, IL-6, or MCP-1 enhanced neurite outgrowth and neural lineage commitment. Results attest to (i) the strong role of activated microglia in regulating NSC fate, (ii) the utility of selective analytes released by activated microglia in promoting neurogenesis and neuritogenesis, and (iii) the need to protect transplanted NSCs from the host inflammatory microenvironment to ensure their survival and functionality in treating neurological disorders.